Communicating and Expressing Emotions in Polish Medieval Texts on the Basis of The Conceptual Dictionary of Old Polish - Sieradzka-Baziur, Bożena (Poznańskie Studia Slawistyczne, 2015)
The linguistic ways of presenting emotions such as communicating and expressing emotions in Polish medieval texts have not been the subject of linguistic analysis. The majority of the oldest linguistic relics are mostly the texts published both in transliterated and transcribed versions and may constitute a basis for large-scale research of vocabulary. Słownik staropolski 1953–2002 (The Dictionary of Old Polish 1953–2002) and resulting The Conceptual Dictionary of Old Polish are a valuable help in the analysis of presenting emotions in medieval texts. The article presents the categories of concepts in The Conceptual Dictionary of Old Polish that concern emotions. The autosemantic continuous and discontinuous units are assigned to 26 conceptual categories concerning emotions. The contents of the category shame from The Conceptual Dictionary of Old Polish are described in order to show the way of presenting data. The general principles of the comprehensive study on communicating and expressing emotions in Polish medieval texts have been formulated.